Underpricing and number of risk factors of initial public offerings in Indonesia - Gumanti, Tatang Ary; Lestari, Ayu Retsi; Manan, Siti Sofia Abdul (Business: Theory and Practice, 2017)
This study examines the effect of number of risk factors, use of proceeds for investment, size of issue and the level of ownership retained on initial returns of firm making Initial Public Offerings (IPOs) in Indonesian capital market. A sample of 290 Indonesia IPOs that went public between 1989 and 2005 were examined. The number of risk factors is found to be positively related to the level of average positive initial returns (underpricing). The level of ownership retention has negative but insignificant relationship with the level of underpricing. Firms that use the proceeds from the offering for investment or expansion purposes are less underpriced than their counterparts that use the funds for operating purposes. Size of issue is negatively associated with the level of underpricing.